1990
DOI: 10.1002/art.1780330220
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness in systemic lupus erythematosus: analysis using the rheumatology attitudes index

Abstract: The Rheumatology Attitudes Index (RAI) was administered to 138 patients with systemic lupus erythematosus (SLE) to determine its reliability and to examine the construct of learned belplessness in patients with this disease. The internal consistency of the RAI was In addition, these data suggest that the learned helplessness construct might be relevant to the outcomes of morbidity and mortality in patients with SLE.Psychological abnormalities and psychosocial dysfunction have been described in patients with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 15 publications
(7 reference statements)
2
59
0
Order By: Relevance
“…our findings are in accordance with the theoretical framework of lH, as well as with results obtained in other studies involving patients with rheumatic diseases [2,6,15]. a significant relationship between distress and lH was also noted in patients with Sle by engle et al [5]. Similar associations between anxiety and depression, measured using HadS, and learned helplessness among patients with rheumatoid arthritis were also noted by lindroth et al [3].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…our findings are in accordance with the theoretical framework of lH, as well as with results obtained in other studies involving patients with rheumatic diseases [2,6,15]. a significant relationship between distress and lH was also noted in patients with Sle by engle et al [5]. Similar associations between anxiety and depression, measured using HadS, and learned helplessness among patients with rheumatoid arthritis were also noted by lindroth et al [3].…”
Section: Discussionsupporting
confidence: 92%
“…moldovan et al [15] reported that lH was related to illness symptoms and consequences, such as pain severity and self-reported general health status. engle et al [5] also noted that more helpless patients experienced more pain and more difficulties in daily activities as a consequence of the illness. Greater functional impairment was also noted among high helpless patients with Sle in comparison with low helpless individuals by Stein et al [16].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, even with this conservative approach, the results are striking. Third, they raise the possibility that, despite the fact that we found no ethnic difference in CRP concentrations (median 3 mg/liter [interquartile range [3][4][5][6][7] in Caucasians compared with 4 mg/liter [interquartile range [3][4][5][6][7] in nonCaucasians; P 檄 0.20), our finding of higher CRP concentrations in obese patients could merely reflect a greater proportion of non-Caucasians in the overweight and obese groups, because some studies have shown higher concentrations of CRP in African Americans. This is not the case; when race (categorized as Caucasian and non-Caucasian) was included in the model, the association between BMI and CRP remained significant (P 辖 0.001 for the unadjusted and all adjusted models).…”
Section: To the Editormentioning
confidence: 98%